Unsteady flow analysis around an elliptic-bladed savonius-style wind turbine - Banerjee, A.; Roy, Sukanta; Mukherjee, P.; Saha, U. (2014)
Although considerable progress has already been achieved in the design of wind turbines, the available technical designs are not yet adequate to develop a reliable wind energy converter especially meant for small-scale applications. The Savonius-style wind turbine appears to be particularly promising for the small-scale applications because of its design simplicity, good starting ability, insensitivity to wind directions, relatively low operating speed, low cost and easy installation. However, its efficiency is reported to be inferior as compared to other wind turbines. Aiming for that, a number of investigations have been carried out to increase the performance of this turbine with various blade shapes. In the recent past, investigations with different blade geometries show that an elliptic-bladed turbine has the potential to harness wind energy more efficiently. In view of this, the present study attempts to assess the performance of an elliptic-bladed Savonius-style wind turbine using 2D unsteady simulations. The SST k-ω turbulence model is used to simulate the airflow over the turbine blades. The power and torque coefficients are calculated at rotating conditions, and the results obtained are validated with the wind tunnel experimental data. Both the computational and experimental studies indicate a better performance with the elliptical blades. Further, the present analysis also demonstrates improved flow characteristics of the elliptic-bladed turbine over the conventional semi-circular design.